Attachment of solid elongated particles on the surface of a stationary gas bubble. (May 2015) - Lecrivain, Gregory; Petrucci, Giacomo; Rudolph, Martin; Hampel, Uwe; Yamamoto, Ryoichi
Graphical abstract: Highlights: Attachment of elongated particles on a gas bubble is investigated. Translational particle velocities are compared with simulated data. Two kinds of attachments, which depend on the collision area, are discovered. Results are relevant to three-phase flow separation processes such as flotation. Abstract: Froth flotation is a separation process which plays a major role in the mining industry. It is essentially employed to recover a vast array of different valuable commodities such as rare earth minerals essential to the manufacture of high-tech products. Owing to its simplicity, the process is also widely used for the de-inking of recycled paper fibres and for the removal of pollutants from waste water. The flotation process essentially relies on the attachment of solid particles on the surface of gas bubbles immersed in water. The present study seeks to investigate the effect of the particle shape on the attachment mechanism. Using an in-house optical micro-bubble sensor the approach, the sliding and the adhesion of micron milled glass fibres on the surface of a stationary air bubble immersed in stagnant water is thoroughly investigated. The translational and rotational velocities were measured for fibres of various aspect ratios. The results are compared with a theoretical model and with experimental data obtained with spherical glass beads. It is found that the fibre orientation during the sliding motion largely depends on the collision area. Upon collision near the upstream pole of the gas bubble the major axis of the fibre aligns with the local bubble surface (tangential fibre alignment). If collision occurs at least 30° further downstream only head of the fibre is in contact with the gas–liquid interface (radial fibre alignment).